Otentisitas di Era Platform: Kajian Multimodal dan Glokalisasi Promosi UMKM Batik Pekalongan-Lasem - Istiningdias, Dini Sri; Ningtyas, Sulistya; Asri, Zietha Arlamanda (Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
This study investigates how micro-entrepreneurs of Pekalongan–Lasem batik negotiate heritage and trendiness in digital promotional language. A corpus of 240 Instagram captions and 80 product visuals posted in 2025 is analyzed through multimodal discourse analysis, appraisal/stance modeling, and corpus-assisted techniques (frequency and collocation) to map lexis, hashtags, and visual framing. The analysis identifies two dominant constellations: a Heritage package foregrounding technique, provenance, and process credibility, and a Glam-Global package emphasizing exclusivity, scarcity, and release tempo. Hybrid glocal forms appear effective yet risk compressing cultural depth into cosmetic signifiers. The article contributes a culturally anchored account of enregisterment within commercial discourse and offers practical guidance for ethical, informative promotion by UMKM and cultural agencies. Implications include protecting indications of origin, strengthening buyer literacy, and encouraging responsible branding within creative economies and sustainability agendas, while offering a reproducible framework for evaluating identity work in small-enterprise marketing across heritage-rich sectors.